Contribution of Foreign Direct Investment to Trade Balance - Dhungel, Bashu Dev (Economic Review of Nepal, 2019)
This article on contribution of foreign direct investment on trade balance in Nepal during the study period 1995–2018 shows the significant positive relationship between inflows of FDI and trade balance. The main objective of this study was to investigate the impact of FDI on trade balance of Nepalese economy. This study has employed Ordinary Least Squares Method to explore relationship between FDI inflows and trade balance in Nepal. The results indicate that there is significant and positive relationship between FDI and trade balance in Nepal. This study has its implication for policymakers to raise FDI inflows to keep the trade balance in Nepalese Economy. To raise the inflows of FDI, it is necessary to make investment friendly environment for foreigners that lead to raise the export and trade moves towards favorable.